Construction and evaluation of chemical structure model of Huolinhe lignite using molecular modeling. Issue 66 (25th August 2017) - Xu, Fang; Pan, Shuo; Liu, Chunguang; Zhao, Deng; Liu, Hui; Wang, Qing; Liu, Ying
Abstract : A lignite molecular model was constructed based on experimental results of multiple techniques, which was then adjusted by concentrations of covalent bonds. Abstract : Molecular model construction plays an important role in gaining insight into the thermal conversion process and reaction mechanism of lignite. Based on element analysis, solid-state 13 C nuclear magnetic resonance ( 13 C NMR), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR), a Huolinhe (HLH) lignite two dimensional (2D) molecular model was initially constructed. Concentrations of main covalent bonds were employed to adjust and examine the molecular model. The advantage of this approach is not only that it can solve the problem of selecting a representative isomer in constructing the model but also that it considers the essence of chemical reaction. The three dimensional (3D) minimum energy configuration was obtained by molecular mechanics (MM) and molecular dynamics (MD) calculation in Materials Studio package (Accelrys). Finally, the sequence of bond-cleavage from DTG analysis and molecular simulations were used to verify the rationality of proposed model. In general, this work has opened pathways in studying the lignite thermal reaction process at the molecular scale.